Evaluation Of Temperature and Lighting in The Dani Bakery Bread Factory - Sambai, Vetherico Arya; Hahury, Sanny; Amri, Irman; Ahistasari, Asih (Journal of Industrial System Engineering and Management, 2023)
This research aims to determine the DANI BAKERY bakery's temperature and lighting measurement results based on Minister of Health Decree Number 1405/MENKES/SK/XI2002. And to find out whether the temperature and lighting measurements results at the DANI BAKERY bakery have met the standards set based on the Decree of the Minister of Health Number 1405/MENKES/SK/XI of 2002. Temperature and lighting levels are evaluated based on the established method. After obtaining data at each measurement point at the research location, the researcher processed and analyzed data. The results of the data analysis will be compared with existing regulations, namely the Decree of the Minister of Health Number 1405/MENKES/SK/XI2002 and also the Decree of the Minister of Health of the Republic of Indonesia NO 70 of 2016 concerning Temperature and Lightning. The evaluation results show that the temperature level measurement results have exceeded the threshold value, namely 33.09℃ - 33.48℃. Meanwhile, the lighting measurement results are below the lighting threshold value, namely 66.89 Lux - 67.67 Lux.